Analisis Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Penyalahgunaan Tanah Negara (Register 45) (Studi Pada Wilayah Hukum Pengadilan Negeri Menggala) - Deni Achmad (Law Faculty of Universitas Bandar Lampung, 2013)
The abuse or misuse of state land in the jurisdiction of the District Court of Menggala is in the Register 45 forest. So the government try again to control the people who inhabit the region,Â precisely in Suwai Umpu (Pekat). The implementation the criminal responsibility towards the state land abuse criminal (register 45) to the jurisdiction ofÂ the District Court of Menggala, besides giving criminal sanctions also requiring responsible person to pay compensation in accordance with the extent of the damage or the consequences thereof to the State, for rehabilitation, forest recovery, or other actions required. The factors to be obstacles in the criminal responsibility towards the state land abuse criminal (in register 45) to the jurisdiction ofÂ the District Court of Menggala are: the limited Forest Guard (police) in maintaining and overseeing the registers 45 forest, the limited number of Civil Servant in handling the violation of the abuse of the state land (register 45), and it is necessary to revise the Law of the Republic of Indonesia Number 41 Year 1999 on Forestry.